(3EbJUGO hJSjjQ GdeDSSIs - (3YHO GdQRGb(B, (3Hf MHjHs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2000)
(3Gdeaghe GdfXGej ddeDSSI(B- (3fXGe GdeDSSI(B- (3fXGe GdJSjjQ GdESJQGJjLj ddeDSSI(B.s
Keywords: (3EbJUGO GdeDSSIs; (3JSjjQ GdeDSSIs